Setting Priorities for Innovation Policy and Evaluating Their Performance: Evidence from Europe and Lessons for Ukraine - Gudrun Rumpf (Foresight and STI Governance)
Setting priorities for supporting prospective technologies and activities is a key issue for science, technology and innovation (STI) policy. The general principles of priority-setting practices vary significantly across countries in terms of process and outcome due to different national cultures, historical prerequisites and rigidities of institutional settings. Often there is a perceived gap between stated policy goals and actual implementation of policy measures. A gap is typical for many developing countries, including Ukraine, in particular,. Ukraine has an established system of laws for STI as well as a solid methodological base for priority setting. Policy aims, however, are not supported by relevant implementation mechanisms, including programmes and framework conditions as well as monitoring and evaluation procedures.